Report of the experience of structuring of a course for primary health care professionals on overweight and obesity in emergency remote learning (Research, Society and Development, 2021)
This text aims to present the experience of collective and interprofessional construction of a teaching plan focused on the care of overweight and obesity in Primary Care in Ceará, carried out between October 2019 and June 2021. Following Holliday's framework, the report was divided into five stages: the starting point, the initial questions contained in the introduction, the recovery of the process experienced, the analysis and critical reflection, contemplated in the methodological path and results, and the arrival points, contained in the final considerations. The interdisciplinary team included professors, researchers and technicians from health services, from different professional categories. After the situational diagnosis, a 180-hour course with three modules was organized: Understanding Overweight and Obesity; Food and Nutrition Surveillance; The Care in Overweight and Obesity. Initially planned for the on-site modality, it needed to be adapted for emergency remote teaching, given the COVID-19 pandemic. The result was the construction of the Guide of the Course on Comprehensive Care for Overweight and Obesity Persons in Primary Health Care, structured into thirteen meetings with synchronous and asynchronous activities, and dispersion actions carried out preferably in the service. We consider the Guide to be a powerful tool for the training and awareness of health professionals in offering more effective and humanized care.